SEDIMENT DISPERSION IN SALMON SPAWNING STREAMS: THE INFLUENCE OF FLOODS AND SALMON REDD CONSTRUCTION1 - Gottesfeld, Allen S.; Hassan, Marwan A.; Tunnicliffe, Jon F.; Poirier, Ron W. (Journal of the American Water Resources Association, 2004)
Magnetically tagged particles were used to investigate the effects of sockeye salmon (Oncorhynchus nerka) and floods on the dispersion of coarse bed material in the Stuart‐Takla region, British Columbia, Canada. The dominant annual sediment transporting event in the channels is the snowmelt flood events, with lesser activity usually accomplished during summer floods. Annually in August, the channel bed material is reworked by the Early Stuart sockeye salmon spawning, as the fish excavate the streambed to deposit and bury their eggs. These nesting cavities are called redds. Results from 67 tracer recovery experiments over five years were highly variable, subject to the magnitude of floods and the returning population of salmon. Overall, the depositional pattern from nival flood events usually demonstrated a high degree of clast mobilization, long travel distances (up to 150 m), and mean depths of burial up to 18 cm. Summer flood events showed somewhat lower rates of mobilization, distances of travel, and depths of burial. Although the fish did not move the tracers very far, their effect on the bed was generally quite pervasive ‐ up to 100 percent of the clasts were mobilized, and the depth of burial was considerable (mean burial depths up to 14 cm). The amount of vertical mixing of sediment by salmon was often on the same order of magnitude as flood events. The significant vertical mixing of sediments by the fish has important implications for the mobility of sediment in the stream. Since any armoring layer formed during high flows throughout the year is subject to the bioturbation of salmon, this suggests that the transport threshold in the creeks remains relatively low. Salmon likely play an integral role in the sediment transport dynamics and annual sediment budget of the lower reaches of these creeks.